Disparities in Vitamin D Status of Newborn Infants from a Diverse Sociodemographic Population in Montreal, Canada. Issue 1 (6th October 2021) - Weiler, Hope A; Vanstone, Catherine A; Razaghi, Maryam; Gharibeh, Nathalie; Patel, Sharina; Wei, Shu Q; McNally, Dayre
ABSTRACT: Background: Vitamin D status at birth is reliant on maternal–fetal transfer of vitamin D during gestation. Objectives: We aimed to examine the vitamin D status of newborn infants in a diverse population and to subsequently identify the modifiable correlates of vitamin D status. Methods: In this cross-sectional study, healthy mother–infant dyads ( n = 1035) were recruited within 36 h after term delivery (March 2016–March 2019). Demographic and lifestyle factors were surveyed. Newborn serum 25-hydroxyvitamin D [25(OH)D] was measured (standardized chemiluminescence immunoassay) and categorized as deficient [serum 25(OH)D <30 nmol/L] or adequate (≥40 nmol/L). Serum 25(OH)D was compared among categories of maternal characteristics using ANOVA; each characteristic was tested in a separate model. Subgroups (use of multivitamins preconception and continued in pregnancy compared with during pregnancy only) were matched ( n = 352/group) for maternal factors (ancestry, age, income, education, parity, and prepregnancy BMI) using propensity scores; logistic regression models were generated for odds of deficiency or adequacy. Results: Infants' mean serum 25(OH)D was 45.9 nmol/L (95% CI: 44.7, 47.0 nmol/L) ( n = 1035), with 20.8% (95% CI: 18.3%, 23.2%) deficient and 60.7% (95% CI: 55.2%, 66.2%) adequate. Deficiency prevalence ranged from 14.6% of white infants to 41.7% of black infants. Serum 25(OH)D was higher ( P < 0.0001) in infants of mothers with higher income, BMI < 25 kg/m 2, exercise and sun exposure in pregnancy, and use of multivitamins preconception. In the matched-subgroup analysis, multivitamin supplementation preconception plus during pregnancy relative to only during pregnancy was associated with lower odds for vitamin D deficiency (ORadj : 0.55; 95% CI: 0.36, 0.86) and higher odds for adequate vitamin D status (ORadj : 1.47; 95% CI: 1.04, 2.07). Conclusions: In this study most newborn infants had adequate vitamin D status, yet one-fifth were vitamin D deficient with disparities between population groups. Guidelines for a healthy pregnancy recommend maternal use of multivitamins preconception and continuing in pregnancy. An emphasis on preconception use may help to achieve adequate neonatal vitamin D status. This trial was registered at clinicaltrials.gov as NCT02563015.